483 The effect of supplemental leucine on regulatory signaling in muscle of growing steers. (7th December 2018) - Pearl, K; Speer, H; Khatri, O; Davis, S; Miesner, M; Gonzalez, J; Titgemeyer, E
Abstract: Leucine in some animal models regulates protein synthesis by intracellular signaling pathways and therefore has potential to increase performance by playing a regulatory role in muscle. Our objective was to determine if leucine supplementation affected mTOR signaling pathway in bovine muscle. Seven ruminally cannulated Holstein steers (173 kg) were used in a 6x6 Latin square design. Treatments, arranged as a 2x3 factorial, included 2 levels of lysine (0 or 6 g/d) and 3 levels of leucine (0, 15, or 30 g/d) infused abomasally. All steers received 2.8 kg/d of a soybean hull-based diet, abomasal infusions of all essential amino acids except lysine (to ensure that lysine was the only limiting amino acid), abomasal infusions of 300 g/d glucose, and ruminal infusions of 350 g/d volatile fatty acids. Longissimus lumborum biopsies were collected on day 7 of each of 6 periods. Using Western Blot analysis, samples were analyzed for total and phosphorylated mTOR, Akt, and 4EBP-1 and total MAFbx and MuRF1. Data were analyzed using the MIXED procedure of SAS; treatment and period were fixed effects, and animal was a random effect. No effects of lysine, leucine, or their interaction were observed for total, phosphorylated, or percentage phosphorylated of mTOR ( P> 0.16) or for total MAFbx ( P> 0.19) or MuRF1 ( P> 0.18). Leucine supplementation linearly ( P= 0.04) increased total Akt, but no treatment differences were observed for phosphorylated Akt ( P> 0.20) or percentage phosphorylated Akt ( P> 0.16). Total and phosphorylated 4EBP-1 were unaffected by treatment ( P >0.15), but percentage phosphorylated 4EBP-1 tended ( P =0.07) to linearly decrease with leucine. Although leucine plays a regulatory role in activating mTOR and interrelated mechanisms in various species, there was not strong evidence of this in bovine muscle. Because leucine supplementation did not change protein deposition in our model, the lack of prominent responses in regulatory signaling is unsurprising.